2017
DOI: 10.1016/j.outlook.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Integrating social context into comprehensive shared care plans: A scoping review

Abstract: BackgroundFailure to address social determinants of health (SDH) may contribute to the problem of readmissions in high-risk individuals. Comprehensive shared care plans (CSCP) may improve care continuity and health outcomes by communicating SDH risk factors across settings.PurposeThe purpose of this study to evaluate the state of knowledge for integrating SDH into a CSCP. Our scoping review of the literature considered 13,886 articles, of which seven met inclusion criteria.ResultsIdentified themes were: integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Finally, the HIE and CDS interventions were not part of a unified package and required additional steps on the part of the care coordinator. Therefore, our recommendations for future research include bundling the CTI interventions into a seamless package that leads to the development of a comprehensive shared care plan (Sullivan, Mistretta, Casucci, & Hewner, ) and deployment regionally as a pragmatic clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the HIE and CDS interventions were not part of a unified package and required additional steps on the part of the care coordinator. Therefore, our recommendations for future research include bundling the CTI interventions into a seamless package that leads to the development of a comprehensive shared care plan (Sullivan, Mistretta, Casucci, & Hewner, ) and deployment regionally as a pragmatic clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Shared care planning is a dynamic process aimed at ensuring patient engagement in healthcare trajectory across time and practice settings [28, 29]. Their goal is to realize a patient – centered care in which especially individuals with complex medical and social needs may receive treatments in accordance with their values, needs, and preferences [30, 31].…”
Section: Specific Pointsmentioning
confidence: 99%
“…6 Unlike implementing direct-care guidelines such as disease screening or surgical checklists, PHP requires a cultural shift to shape care around patient priorities. 3,6,10 This shift is similar to the implementation of other complex initiatives including PCMH, requiring buy-in, role negotiation, coordination, and integration with clinical informatics. [17][18][19][20][21][22][23] Although research on challenges specific to personalized care planning implementation is limited, one feasibility study of PHP identified similar challenges.…”
Section: Introductionmentioning
confidence: 98%
“…Personalized care planning, a process to collaboratively develop care plans tailored to patient priorities and social contexts, is increasingly important to providing high-quality, patientcentered care. [1][2][3] Despite varying contents and terminologies (e.g., personalized care plans, comprehensive shared care plans), these approaches incorporate common elements including (a) patient-provider discussions to identify goals; (b) development of holistic plans that attend to clinical and nonclinical needs; and (c) mechanisms to share plans across providers to coordinate care. 1 Consonant with goal-directed care, these plans are designed to align healthcare with what matters most to patients, shifting away from a disease-oriented paradigm.…”
Section: Introductionmentioning
confidence: 99%